Spring Meetings 2022 Media Roundtable Opening Remarks by World Bank Group President David Malpass - Malpass, David (World Bank, Washington, DC, 2022)
This report discusses the remarks delivered by World Bank Group President David Malpass at the spring meetings 2022 media roundtable opening. He discusses on Coronavirus disease 2019 (COVID-19), inflation, and Russia’s invasion of Ukraine.